Vulnerability and socio-ecological risks: an integrated perspective of risks in Guaratiba region (Rio de Janeiro – Brazil) - Lima, Maria Luciene da Silva; Solórzano, Alexandro; Rego, Luiz Felipe Guanaes; Freitas, Marcelo Motta de; Porto, Bianca Pereira Alvim (Sociedade & Natureza, 2021)
Through almost five centuries of occupation and the resulting processes of landscape transformation, ecological scenarios in the neighborhood of Guaratiba have become areas of production, residence, and urban transition. This historicity is a key element to understand local vulnerabilities and associated risks. Thus, within the scope of landscape management and under an integrative approach of vulnerabilities and risks, our objective in this study is to map and analyze socio-ecological vulnerabilities and risks in the study area. Research was structured on i) investigating the history of landscape use, occupation and transformation, ii) identifying vulnerable areas, and iii) classifying socio-ecological risks. Three methodological steps were used: (1) analysis of historical processes of land use and occupation in Guaratiba; (2) delimitation of Socio-ecological Landscape Units (SELU) in order to understand current levels of heterogeneity in the study area; and (3) modeling and characterization of identified socio-ecological risks. Based on the geoprocessing technique known as fuzzy logic, analysis led to a socio-ecological classification of risks, recognizing that such phenomena can only be understood by examining human presence in face of the relevance of events which can harm exposed groups. The investigation showed that four out of six delimitated landscape units have points on which there is a tendency of risks: SELU 2, SELU 4, SELU 5, and SELU 6. These areas suggest socio-ecological risks of the physical type, related to geomorphologic (landslides and floods) and environmental health dynamics.